Characterization of particles from a marine engine operating at low loads. (January 2015) - Anderson, Maria; Salo, Kent; Hallquist, Åsa M.; Fridell, Erik
Abstract: Particle emissions from a marine diesel engine operating at low loads with four different fuels were characterized with respect to particle number (PN) and particle mass (PM), size distribution, volatility and chemical composition. The four different fuels used were Swedish Environmental class 1 (MK1) and class 3 diesel (MK3), heavy fuel oil (HFO, 0.12 wt% S) and marine diesel oil (MDO, 0.52 wt% S). The measurements were performed for a marine diesel engine in a test-bed engine lab and the particle emissions were measured with an Engine Exhaust Particle Sizer and a Dust Monitor, giving the number concentrations in the size range of 5.6–560 nm and 300 nm to 20 μm, respectively. To quantify the amount of solid particles a thermodenuder was used. Additionally, filter samples were taken for gravimetric, black carbon (BC) and elemental analysis. The particle emissions showed a bimodal size distribution by number and the number concentrations were dominated by nanoparticles (diameter (Dp) < 50 nm). The nanoparticles measured were both primary and secondary particles, depending on fuel and engine load, while the particles with Dp > 50 nm generally were solid primary particles. Combustion of HFO resulted in the highest PN and PM concentrations. Emission factors (EFs) for PM and PN for both the total particle emissions and the fraction of primary, solid particles are presented for different fuels and loads. EFs for nitrogen oxides (NO x ), BC and some elements (Ca, Fe, V, Ni, Zn) are presented as well. This study contributes to understanding particle emissions from potential future fuels as well as emissions in ports and coastal areas where lower engine loads are common. Highlights: Measurements of particle emissions from low sulfur marine fuels. Measurements conducted on a test-bed engine operating at low engine loads. Nanoparticles (Dp < 50 nm) were the dominating fraction of total particle number. Particle formation is not only related to the sulfur content of the fuel.